Towards a community engagement turn? Historians debate forms of engagement in 21st century-higher education - Elize S. van Eeden (Contree, 2021)
Should the luxury we currently enjoy of focusing our research mainly on debating and/or philosophising about the discipline of History in centres of Higher Education and Training (HET) not be transformed in the 21st century? Recently, the trend is that community engagement in these environments should become infused with the tertiary education sector vision by means of engaged research; and engaged, teaching and learning, and that HET scholarship should focus on community engagement that complements sustainable livelihoods. With this in mind a webinar was organised by North-West University’s Regional History Research Group. This was held on 29 November 2021, with the title “Engaging community/ies in regional histories research: Sharing experiences and best practice.” Prof Sulevi Riukulehto (Finland), and Prof Sekibakiba Lekgoathi (University of the Witwatersrand) were among the prominent speakers. Interesting ideas and experiences of working with communities were discussed and ideas were put forward on community engagement in the process of fieldwork.